Can Switching Between Inflationary Regimes Explain Fluctuations in Real Interest Rates? - Bleaney, M. (IMF Working Papers; Working Paper ;, 1997)
It has recently been suggested that allowing for switches between different inflationary regimes produces a much better fit for the Fisher relationship between interest rates and inflation, at least for U.S. data. The paper assesses the merits of the regime-switching theory as an explanation for the apparent fluctuations in real interest rates in Australia, Canada, Germany, the United Kingdom, and the United States.